2000
DOI: 10.1177/106939710003400103
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Cultural Tightness and Collectivism on Self-Concept and Causal Attributions

Abstract: Previous research investigating the influence of cultural variables on the psychological constructs of self-concept and causal attributions has employed responses of individuals within cultures. In the present research, ethnographies of 16 cultures were examined using the CD-ROM version of the Human Relations Area Files (HRAF). As predicted, self-concept was related to both cultural tightness and collectivism. Specifically, interdependent self-concepts were more likely to occur in tight and collective cultures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
115
1
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(120 citation statements)
references
References 28 publications
2
115
1
2
Order By: Relevance
“…We collected a wide range of variables from different databases (e.g., DDB Lifestyle Survey, US Census Bureau, Gallup, General Social Survey) to test the validity of the index (see Table S5 for specific variables and associated databases). Consistent with previous research (15,20), the index was only moderately correlated with collectivism, or the degree to which individuals are interdependent with their families and in-groups [r (49) = 0.37, P < 0.01]. Because Hawaii was a statistical outlier relative to all other states on Vandello and Cohen's (3) collectivism index, we excluded it from the analysis; when Hawaii is included in the analysis, the correlation between tightness and collectivism is r (50) = 0.23, P = 0.11.…”
Section: Significancesupporting
confidence: 82%
“…We collected a wide range of variables from different databases (e.g., DDB Lifestyle Survey, US Census Bureau, Gallup, General Social Survey) to test the validity of the index (see Table S5 for specific variables and associated databases). Consistent with previous research (15,20), the index was only moderately correlated with collectivism, or the degree to which individuals are interdependent with their families and in-groups [r (49) = 0.37, P < 0.01]. Because Hawaii was a statistical outlier relative to all other states on Vandello and Cohen's (3) collectivism index, we excluded it from the analysis; when Hawaii is included in the analysis, the correlation between tightness and collectivism is r (50) = 0.23, P = 0.11.…”
Section: Significancesupporting
confidence: 82%
“…Carpenter (2000) supported this supposition in a study of ethnographies of 16 traditional societies in the Human Relations Area Files. She found that individualism-collectivism and tightness-looseness were only moderately correlated (r=.44).…”
Section: Tightness-looseness Definedmentioning
confidence: 82%
“…Although, prima facie, the concept of tightness-looseness appears parallel to the cultural dimension of individualism-collectivism, the two are distinct (Carpenter, 2000;Triandis, 1989). Individualism-collectivism is concerned with the emphasis placed by societies on strong in-group ties versus being independently oriented -it does not refer to how much tolerance there is for deviance from norms.…”
Section: Culture and Leadershipmentioning
confidence: 99%